2009
DOI: 10.1089/vim.2008.0071
|View full text |Cite
|
Sign up to set email alerts
|

Listeria monocytogenesDelivery of HPV-16 Major Capsid Protein L1 Induces Systemic and Mucosal Cell-Mediated CD4+and CD8+T-Cell Responses After Oral Immunization

Abstract: Neutralizing antibodies are thought to be required at mucosal surfaces to prevent human papillomavirus (HPV) transmission. However, the potential for cell-mediated immunity in mediating protection against HPV infection has not been well explored. We generated recombinant Listeria monocytogenes (Lm) constructs that secrete listeriolysin O (LLO) fused with overlapping N-terminal (LLO-L11–258) or C-terminal (LLO-L1238–474) fragments of HPV type 16 major capsid protein L1 (HPV-16-L1). Oral immunization of mice wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…Here we show that CD4+ T cell help plays an important role in the enhancement of antigen-specific CD8+ T cell immune responses observed in our vaccination regimen as co-administration with the reverse sequence of BPV1 L1 or L2 did not enhance the antigen-specific CD8+ T cell responses. Studies have shown that L1 and L2 are generally much more effective in eliciting CD4+ T cell responses [14][15][16][17][18]. While it is possible that BPV L1 or L2 could elicit some CD8+ T cell responses, we Fig.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Here we show that CD4+ T cell help plays an important role in the enhancement of antigen-specific CD8+ T cell immune responses observed in our vaccination regimen as co-administration with the reverse sequence of BPV1 L1 or L2 did not enhance the antigen-specific CD8+ T cell responses. Studies have shown that L1 and L2 are generally much more effective in eliciting CD4+ T cell responses [14][15][16][17][18]. While it is possible that BPV L1 or L2 could elicit some CD8+ T cell responses, we Fig.…”
Section: Discussionmentioning
confidence: 69%
“…In the current study, we aim to combine intracellular targeting strategies using CRT with a strategy to enhance CD4 + T help for the development of a therapeutic HPV DNA vaccine. Since papillomavirus L1 or L2 antigens likely contain CD4 + T cell epitopes [14][15][16][17][18], we reasoned that co-administration of vectors containing codon-optimized bovine papillomavirus (BPV) L1 and L2 may provide CD4 + T cell help and enhance the antigenspecific CD8 + T cell immune responses generated by DNA vaccines. An additional potential benefit would be the induction of neutralizing antibody and protective immunity [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…L. monocytogenes antigen processing and presentation via the major histocompatability complex class I pathway makes it an attractive vector for delivery of viral and cancer antigens. Animal studies show that L. monocytogenes vectors can generate T cell‐mediated immune responses to lymphocytic choriomeningitis virus, influenza virus, HIV‐1 Gag, and human papilloma virus‐16 antigens (1–5). Despite these promising results, there are safety concerns related to using recombinant wild type L. monocytogenes as a vaccine vector due to the high degree of morbidity and mortality that results from naturally acquired infection.…”
mentioning
confidence: 99%
“…Simply, L. monocytogenes stimulates antigen-specific CD8+ and CD4+ T cell responses following its evasion of immune destruction by releasing Lm toxin to avoid phagosomal lysis. However, the most appealing factor of the L. monocytogenes vector is that the immune response can be easily controlled by antibiotics should the body react adversely to Lm [101][102][103][104]. With regards to viral vectors, a few viruses, such as the vaccinia virus, adenovirus, vesicular stomatitis virus, and alphavirus, have distinguished themselves and show great promise.…”
Section: Molecular Therapies In Developmentmentioning
confidence: 99%